THE SOCIO-ECONOMIC IMPACT OF FASCIOLIASIS DISEASE IN NANDI CENTRAL DISTRICT, KENYA - Ngaira, V. M. (Archives of Business Research, 2016)
The study was carried out in Nandi Central in Nandi County to evaluate the economic impact of fascioloasis disease and it’s prevalence amongst cattle, sheep and goats in three divisions namely Kapsabet, Kosirai and Kilibwoni. The named divisions have a sizeable coverage by papyrus a swab which is home to the snail species lymnae trancatum and lymnae trancatula which are vectors of the disease as the intermediate host.The research design was a survey and sampling technique used was purposeful sampling. Secondary data was collected from Kapsabet District Veterinary Office on the number of condemned liver from the cattle, keep and goats and financial losses were computed based in the price of the respective livers of each species and data analysis was done using SPSS Version 16. Mean separation was done using L.S.D (P< 0.05). A total of 1106 livers were condemned comprising of 721 (Bovine Spp); 342 (Ovine Spp) and 43 (Caprine Spp), which translated to arrival financial losses of 823,060.There was significant difference of fascioliasis between Kosirai and both Kilibwoni and Kapsabet. Bovine Spp had the highest incidence followed by Ovines Spp and finally Caprine Spp. It was also found that there was a positive correlation between the incidents rate and livers condemned and the usually high rainfall seasons of around March-October